The Svalbard Treaty and Norwegian Sovereignty - Øystein Jensen (Arctic Review on Law and Politics, 2020)
A hundred years ago on 9 February 2020, the Svalbard Treaty was adopted in Paris, granting Norway her long-standing ambition: full and absolute sovereignty over the Svalbard archipelago. After a brief review of the negotiations that preceded the Paris decision, this article examines the main elements of the Treaty: Norwegian sovereignty, the principle of non-discrimination and the terra nullius rights of other states, peaceful utilization, scientific research and environmental protection. Focus then shifts to Norway’s policy towards Svalbard and the implementation of the Treaty’s provisions: what have been the main lines of Norwegian Svalbard politics; what administrative structures have evolved; to what extent has Norwegian legislation been made applicable to Svalbard? Importantly, the article also addresses how widespread changes in international law that have taken place since 1920, particularly developments concerning the law of the sea, have brought to the forefront controversial issues concerning the geographic scope of the Treaty’s application.